2012
DOI: 10.1071/sh11095
|View full text |Cite
|
Sign up to set email alerts
|

Condom use errors and problems: a global view

Abstract: Abstract. Background: Significantly more research attention has been devoted to the consistency of condom use, with far fewer studies investigating condom use errors and problems. The purpose of this review was to present the frequency of various condom use errors and problems reported worldwide. Methods: A systematic literature search was conducted for peer-reviewed articles, published in English-language journals between 1995 and 2011. Results: Fifty articles representing 14 countries met criteria for inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
143
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(159 citation statements)
references
References 55 publications
8
143
1
7
Order By: Relevance
“…Traditionally, BCT have assumed that the vulnerability to HIV of WACB was caused by condom use errors and problems: a lack of skills, negative attitudes and norms, a lack of perceived control over sexual practices and because they did not feel vulnerable to HIV or did not believe in the condom's effectiveness to reduce the risk [23][24][25][26][27][28][29][30][31]. In short, BCT conceptualize risk behaviors as an individual's deliberate choice, yet fail to consider relational, social, and cultural aspects of sexual risk behaviors.…”
Section: Vulnerability Of Wacb To Hivmentioning
confidence: 99%
“…Traditionally, BCT have assumed that the vulnerability to HIV of WACB was caused by condom use errors and problems: a lack of skills, negative attitudes and norms, a lack of perceived control over sexual practices and because they did not feel vulnerable to HIV or did not believe in the condom's effectiveness to reduce the risk [23][24][25][26][27][28][29][30][31]. In short, BCT conceptualize risk behaviors as an individual's deliberate choice, yet fail to consider relational, social, and cultural aspects of sexual risk behaviors.…”
Section: Vulnerability Of Wacb To Hivmentioning
confidence: 99%
“…O uso de métodos hormonais que sejam compatíveis com uso das terapias antirretrovirais e que possam trazer melhorias clínicas associadas ao uso regular de condom como método de barreira é o desejável 3 . A adesão à dupla contracepção permanece um desafio para a população geral, grupos vulneráveis e entre pessoas infectadas por doença sexualmente transmissível (DST)/HIV/AIDS 4,5 . A taxa de adesão à dupla contracepção referida entre mulheres infectadas pelo HIV gira em torno de 27% 6,7 , com chance maior que três vezes de engravidar de modo não planejado entre as não usuárias de dupla proteção contraceptiva 8 .…”
Section: Introductionunclassified
“…CarloS alBerTo lima da Silva 5 Resumo OBJETIVO: Verificar a adesão à dupla contracepção entre mulheres infectadas pelo HIV usando acetato de medroxiprogesterona de depósito (AMPD) e condom. MÉTODOS: Corte transversal realizado em centro de referência de dezembro 2013 a setembro 2014.…”
unclassified
“…Proper use has been shown to decrease HIV transmission by 80% [7] and HPV transmission by 70%, [8] however most patients do not use condoms properly. A systematic review found that incomplete use (such as late application or early removal) occurred 17.0% to 51.1% of the time, while other improper techniques (like leaving no space at the tip) ranged from 24.3% to 45.7% [9].…”
mentioning
confidence: 99%